Oleuropein has hypophagic effects in broiler chicks - Sulaiman, Usman; Vaughan, Reagan; Siegel, Paul; Liu, Dongmin; Gilbert, Elizabeth Ruth; Cline, Mark Andrew (Frontiers in Physiology, 2024)
Oleuropein, a phenolic compound derived from olives, has known glucoregulatory effects in mammalian models but effects in birds are unknown. We investigated effects of dietary supplementation and exogenous administration of oleuropein on broiler chick feed intake and glucose homeostasis during the first 7 days post-hatch. One hundred and forty-eight day-of-hatch broiler chicks were randomly allocated to one of four dietary treatments with varying oleuropein concentrations (0, 250, 500, or 1000 mg/kg). Body weight and breast muscle and liver weights were recorded on day 7. In the next experiment, chicks received intraperitoneal (IP) injections of oleuropein at doses of 0 (vehicle), 50, 100, or 200 mg/kg on day 4 post-hatch, with feed intake and blood glucose levels measured thereafter. Lastly, chicks fed a control diet were fasted and administered intracerebroventricular (ICV) injections of oleuropein at doses of 0, 50, 100, or 200 μg, after which feed intake was recorded. Results indicated that IP and ICV injections led to decreased feed intake, primarily at 60 minutes post-injection, with effects diminishing by 90 minutes in the IP study. Blood glucose levels decreased 1-hour post-IP injection at higher oleuropein doses. These findings suggest that oleuropein acts as a mild appetite suppressant and influences energy metabolism in broiler chickens.